Relationship between service quality and customer satisfaction: A systematic literature review - Bakri, Mohammed Hariri; Ismail, Ashari; Rusli, Norsahiat; Abu Bakar, Mohammad Aqmal; Othman, Habibullah (Institute For Advanced Studies, 2023)
This article aims to conduct a systematic literature review of the relationships between service quality and customer satisfaction. Forty-one papers were chosen after a search was performed in the Web of Science and Scopus databases. The findings indicate a significant relationship between service quality and customer satisfaction, including direct and indirect correlations. Avariety of direct and indirect relationships between service quality and customer satisfaction are suggested in light of these findings. The finding contributes to the few earlier studies on these collaborative relationships.